Changes in breast sensitivity at puberty, during the menstrual cycle, and at parturition. Issue 6070 (7th May 1977) - Robinson, J E; Short, R V
Abstract : Sensitivity to pain and touch was measured in the nipple, areola, and cutaneous breast tissue of prepubertal boys and girls, postpubertal men and nuliparous women before and after delivery. Before puberty there were no differences between the sexes, but after puberty the tactile sensitivity of all areas of the women's breast was significantly greater than the men's. Tactil sensitivity of all areas also varied during the menstrual cycle, with maximal sensitivity at midcycle and at menstruation; the mid-cycle peak was absent when the women were taking oral contraceptives. But the most dramatic changes occured within 24 hours of parturition, when there was a great increase in breast sensitivity. This may be the key event for activating the suckling-induced discharge of oxytocin and prolactin and inhibiting ovulation during lactation.